Coast guard rescue one eaudiobook - Debrabandere, Natalie (Tantor Media, 2019)
Army Capt. Jordan Armstrong surrendered a piece of her soul to the burning sands of Afghanistan. Now back home, only two things keep her going: her demanding job as a Search and Rescue pilot and sailing her forty-five-foot yacht around the coast of McKinley Point, Western Australia—alone. Plenty of women have tried to reach behind her walls, but Jordan remains aloof. When American expat Sara Matthews shows up in her life and takes an instant dislike to her, it sets her heart on fire. For the first time in what feels like forever, Jordan truly wants to be seen and understood. She desperately wants Sara to discover the real person behind the mask. And so, it begins . . . Contains mature themes.